O que está acontecendo? um estudo designativo das hashtags à luz da semântica do acontecimento - Silva, Valter Correia da (2021)
In this work, we try to approach with the Twitter hashtag from an enunciative designation point of view, considering it beyond its notion of a tagging tool, in order to classify the micromessages posted on the social network. To this, we develop a path through the event in which the hashtag acquires meaning and examine which elements are involved in this process, going through different linguistic, historical and anthropological notions that deal with hashtags, and presenting the Twitter genre from its concept as a social network. As a theoretical and methodological contribution, we base ourselves on the assumptions of the Semantics of the Event of Guimarães (2002) and on the Semantic Domain of Determination (DSD), the author's method of analysis to arrive the designation of an utterance. Other semantics scholars are also important for this research, due to the dialogue that Guimarães establishes with them when developing his theoretical proposal, such as Bréal, Benveniste, Ducrot. Our proposal was to analyze the designation process of utterances on Twitter from hashtags, observing how their meaning process occurs depending on how the utterances in which they are inserted are integrated, as text elements. Likewise, to describe and analyze the processes of designation of hashtags, here taken as nominal forms, also identifying their relationships with the tweet in which they are inserted, examining how and in what way these names are constituted based on the articulation carried by the pertinence between the memorable and the actuality of the event of the utterances. As a result, we selected as corpus of analysis 6 (six) tweets published on the social network during the period from march 1, 2020 to march 31, 2020, and we examined how the meaning of the utterance is constituted from the carried articulation for the pertinence between the memorable and the actuality of the event of these statements. In the analysis, we observe how two relationships occur: between their designation and naming, paying attention to the relationship with the utterances produced by platform users, thus constituting language events, in which the operation of certain names linked to certain hashtags are cut as memorable by specific temporalities; and between designating and referring, paying attention to how the hashtag of a tweet is related, by textuality, to other names working under the guise of substitutability, determining and predicating them. With the analysis, we show that, in this process of constitution of meaning, there is a dynamics of agency to which the political is inseparable, and which characterizes a conflict on the scene, a conflict of speech, conferring a sharing of the real from the relationship of places to say in the enunciative scene and its relationship with the designation of the utterances, constituted by the argumentativeness itself in the construction of the text, through certain modes of relationship, such as repetition, substitution, etc. observed in the analyzed statements.